Skills Gaps and the Path to Successful Skills Development : Emerging Findings from Skills Measurement Surveys in Armenia, Georgia, FYR Macedonia, and Ukraine - World Bank Group (World Bank, Washington, DC, 2015)
Relevant skills for the job market—the ability to do well a job that is also in demand—are becoming an important bottleneck to private sector growth in many countries in the former Eastern Europe and Central Asia (ECA) region. Economic reforms together with structural and technological change are bringing about new business opportunities and with them demand for new skills. A new take on skills development is needed to help increase productivity, job creation, and wages. The different stakeholders—policy makers that coordinate the strategy around skills and education, workers, the jobless, students and their families who make decisions to invest in training, and firms—need to coordinate around the skills agenda.